Phytochemistry of Centaurea saligna: silver nanoparticle synthesis, quantification of natural compounds, antioxidant and antibacterial activity - Esma Nur Gecer (Scientific Reports)
Abstract Centaurea species contain medicinally bioactive compounds. The capping, stabilization, and reduction of silver ions by the bioactive compounds in Centaurea saligna are crucial for the formation of silver nanoparticles. Nanotechnology, with its wide-ranging applications, is a significant discipline in science. Due to the widespread application of nanoparticles, many studies have been conducted. Herein, silver nanoparticles (AgNPs@cs) were produced via leaves of Centaurea saligna, and quantification of phenolics existing in leaves was established by LC–MS/MS. Furthermore, antioxidant and antibacterial activities were conducted for both the extract and the nanoparticles. The analytical techniques, including FTIR, UV–VIS, XRD, and TEM, were employed to elucidate the structure. Moreover, stability was determined by measuring the zeta potential. Scutellarin (8.67 mg/g extract), shikimic acid (3.97), and chrysin (2.67) were found as major compounds by LC–MS/MS. In DPPH radical scavenging activity, AgNPs@cs displayed an excellent effect (IC50, μg/mL, 9.27 ± 0.14) in association to BHT (12.45 ± 0.41, IC50, μg/mL). In addition, AgNPs@cs showed good activity against the tested bacteria. The absorption in UV–Vis analysis at 441 nm displayed nanoparticle formation. The size of the nanoparticle was calculated using TEM and XRD measurements, which were 16.2 nm and 18.5 nm, respectively. The zeta potential measurement confirmed the stability. It may be possible to use Centaurea saligna in the production of foods and medications.